Jual Beli Plat Nomor Kendaraan Bermotor Perspektif Fiqih Muamalah dan Undang-Undang LLAJ di Bondowoso - Miftahur Riski (Sharia Faculty, Kiai Haji Achmad Siddiq State Islamic University of Jember, 2020)
Buying and selling is a form of interaction between people to maintain and fulfill their daily needs. Buying and selling vehicle number plates can be found in the Bondowoso area. The sale and purchase of motorized vehicle number plates on the side of the road is permitted according to religion and law. However, in practice many people make these number plates with various purposes in which there are elements of fraud and forgery. To trick the police by ordering a beautiful number plate that is attached to a bulging motorbike, to be modified, originally on the plate the numbers are converted into letters, to change their validity period. The purpose of this study was to determine how the practice of buying and selling motor vehicle number plates in Bondowoso in terms of fiqh muamalah and Law Number 22 Year 2009 concerning Traffic and Road Transport. The method used in this research is descriptive qualitative with a field research approach.